2021
DOI: 10.1177/03000605211016627
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal hypertension and increased acute kidney injury risk: a systematic review and meta-analysis

Abstract: Objective The present meta-analysis aimed to determine the relationship between intra-abdominal hypertension (IAH) and an increased prevalence of acute kidney injury (AKI) and identify the associated risk factors in various patient populations, regardless of whether they were admitted to an intensive care unit. Methods We used three databases for the following search terms: “IAH,” “abdominal compartment syndrome,” “AKI,” “acute kidney failure,” and others. The articles retrieved were compared to identify appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…In recent years, due to the gradual increase in mortality of ACS and IAH, effective treatment of them has attracted increasing attention [1,2]. So far, abdominoplasty is still an effective measure for the treatment of IAH [3]. e therapeutic botulinum toxin type A is artificially extracted from botulinum toxin type A. e efficacy and safety of BoNT-A injection therapy have been affirmed by the academic community and the industry [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, due to the gradual increase in mortality of ACS and IAH, effective treatment of them has attracted increasing attention [1,2]. So far, abdominoplasty is still an effective measure for the treatment of IAH [3]. e therapeutic botulinum toxin type A is artificially extracted from botulinum toxin type A. e efficacy and safety of BoNT-A injection therapy have been affirmed by the academic community and the industry [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to patients without IAH, patients with IAH had a higher risk of AKI (odds ratio = 2.57, 95% confidence interval: 1.55-4.26, P < 0.001). In the subgroup and meta-regression analyses, body mass index, age, the presence or absence of burns, and cardiac surgery did not affect the risk of AKI [28]. A singlecenter prospective cohort study conducted on 42 patients undergoing cardiac surgery with cardiopulmonary bypass, in whom IAP was measured prior to surgery, immediately after surgery in the operating room and at post-operative 3-6-12-24 h, showed that 83.3% of them developed IAH [29].…”
Section: Intra-abdominal Hypertension and Abdominal Compartment Syndr...mentioning
confidence: 83%
“…[ 10 , 15 , 16 ] The meta-analysis recently confirmed that IAH increases AKI risk. [ 17 ] IAH caused reduction in arterial inflow and venous outflow from kidney, then reduction in renal perfusion had developed. Reduction in glomerular hydrostatic pressure from renal hypoperfusion additional with increased Bowman space hydrostatic pressure from intraabdominal hypertension may result in reduction in glomerular filtration gradient which may be the cause of AKI.…”
Section: Discussionmentioning
confidence: 99%